4(3-х)+5<3(x+2)-7 = 12-4x+5<3x+6-7 = -4x-3x<6-7-12-5 = -7<-18
3(2+x)-4>2(x-1)+5 = 6+3x-4>2x-2+5 = 3x-2x>-2+5-6+4 = x>1
Дальше надо график чертить, если сказано.
-7-18x
x (перевернутая) э = (- бесконечность, - 7)
1x
x (перевернутая) э = ( 1, +бесконечность)
4(3-х)+5<3(x+2)-7 = 12-4x+5<3x+6-7 = -4x-3x<6-7-12-5 = -7<-18
3(2+x)-4>2(x-1)+5 = 6+3x-4>2x-2+5 = 3x-2x>-2+5-6+4 = x>1
Дальше надо график чертить, если сказано.
-7-18x
x (перевернутая) э = (- бесконечность, - 7)
1x
x (перевернутая) э = ( 1, +бесконечность)